Clinical and preclinical therapeutic outcome metrics for USH2A-related disease. (30th January 2020) - Toms, Maria; Dubis, Adam M; de Vrieze, Erik; Tracey-White, Dhani; Mitsios, Andreas; Hayes, Matthew; Broekman, Sanne; Baxendale, Sarah; Utoomprurkporn, Nattawan; Bamiou, Doris; Bitner-Glindzicz, Maria; Webster, Andrew R; et al.
Abstract: USH2A variants are the most common cause of Usher syndrome type 2, characterized by congenital sensorineural hearing loss and retinitis pigmentosa (RP), and also contribute to autosomal recessive non-syndromic RP. Several treatment strategies are under development; however, sensitive clinical trial endpoint metrics to determine therapeutic efficacy have not been identified. In the present study, we have performed longitudinal retrospective examination of the retinal and auditory symptoms in (i) 56 biallelic molecularly confirmed USH2A patients and (ii) ush2a mutant zebrafish to identify metrics for the evaluation of future clinical trials and rapid preclinical screening studies. The patient cohort showed a statistically significant correlation between age and both rate of constriction for the ellipsoid zone length and hyperautofluorescent outer retinal ring area. Visual acuity and pure tone audiograms are not suitable outcome measures. Retinal examination of the novel ush2a u507 zebrafish mutant revealed a slowly progressive degeneration of predominantly rods, accompanied by rhodopsin and blue cone opsin mislocalization from 6 to 12 months of age with lysosome-like structures observed in the photoreceptors. This was further evaluated in the ush2a rmc zebrafish model, which revealed similar changes in photopigment mislocalization with elevated autophagy levels at 6 days post fertilization, indicating a more severe genotype-phenotype correlation and providing evidence of new insights into the pathophysiology underlying USH2A -retinal disease.